The Effects of Sports Drinks During High-Intensity Exercise on the Carbohydrate Oxidation Rate Among Athletes: A Systematic Review and Meta-Analysis - Li, Xudong; Wang, Wanxia; Guo, Rui; Wang, Anqi; Wei, Chaojun (Frontiers in Physiology, 2020)
Background: This study examines the effects of sports drinks ingestion during high-intensity exercise for carbohydrate oxidation rate (CHO-O) among athletes. Methods: PubMed, Embase, and the Cochrane library were searched for available papers published up to November 2019. The primary outcome is the carbohydrate oxidation rate (CHO-O), and the secondary outcome is the fat oxidation rate (Fat-O). Statistical heterogeneity among the included studies was evaluated using Cochran's Q test and the I2 index. The random-effects model was used for all analyses, regardless of the I2 index. Results: Five studies are included, with a total of 58 participants (range, 8–14/study). All five studies are randomized crossover trials. Compared to the control beverages, sports drinks have no impact on the CHO-O of athletes [weighted mean difference (WMD) = 0.29; 95% CI, −0.06 to 0.65, P = 0.106; I2 = 97.4%, P < 0.001] and on the Fat-O of athletes (WMD = −0.074; 95% CI, −0.19 to 0.06, P = 0.297; I2 = 97.5%, P < 0.001). Carbohydrate–electrolyte solutions increase CHO-O (WMD = 0.47; 95% CI, 0.08–0.87, P = 0.020; I2 = 97.8%, P < 0.001) but not Fat-O (WMD = −0.14; 95% CI, −0.31 to 0.03, P = 0.103; I2 = 98.2%, P < 0.001). Caffeine has a borderline effect on Fat-O (WMD = 0.05; 95% CI, 0.00–0.10, P = 0.050). Conclusions: Compared with the control beverages, sports drinks show no significant improvement in CHO-O and Fat-O in athletes. Carbohydrate–electrolyte solutions increase CHO-O in athletes but not Fat-O.